Diffusion Tensor Imaging of the Calf Muscles in Subjects With and Without Diabetes Mellitus. Issue 5 (19th September 2018) - Edalati, Masoud; Hastings, Mary K.; Sorensen, Christopher J.; Zayed, Mohamed; Mueller, Michael J.; Hildebolt, Charles F.; Zheng, Jie
Abstract : Background: Diffusion tensor imaging (DTI) has been used to characterize calf skeletal muscle architecture. Purpose: To assess the diffusional properties of the calf muscles of subjects with and without diabetes, at rest and during isometric plantarflexion exercise. Study Type: Prospective. Subjects: Twenty‐six subjects in two groups: 13 healthy and 13 subjects with type 2 diabetes (DM); each group consisted of seven females and six males. Field Strength/Sequence: 3T/2D single‐shot spin echo planar imaging. Assessment: Fractional anisotropy (FA), mean diffusivity (MD), diffusion eigenvalues, and fiber tracking indices were obtained from the medial gastrocnemius (MG), lateral gastrocnemius (LG), and soleus (SOL) muscles of the calf at rest and during isometric plantarflexion exercise. Statistical Tests: We used a combination of nonparametric (Wilcoxon) and parametric ( t ‐test) statistical assessments. Results: The medial gastrocnemius muscle had more indices with significant differences between the two groups (six indices with P  < 0.05) than did the lateral gastrocnemius (three indices with P  < 0.05) and soleus muscles (only one index with P  < 0.05). While the healthy group showed elevated MD values from rest to exercise (MG = 5.83%, LG = 13.45%, and SOL = 11.68%), the diabetic MD showed higher increases (MG = 19.74%, LG = 29.31%, and SOL = 20.84%) that were different between groups (MG: P  = 0.009, LG: P  = 0.037, and SOL: P  = 0.049). Data Conclusion: Our results indicate considerable diffusional changes between healthy subjects and subjects with diabetes at rest and during isometric plantarflexion exercise in the calf muscles. The medial gastrocnemius muscle displayed the most diffusion sensitivity to diabetes‐related microstructural changes. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:1285–1295.